Review of Best Practices for CLABSI Prevention and the Impact of Recent Legislation on CLABSI Reporting. (November 2016) - Woodward, Benjamin; Umberger, Reba
Central line-associated bloodstream infections (CLABSI) are a very common source of healthcare-associated infection (HAI). Incidence of CLABSI has been significantly reduced through the efforts of nurses, healthcare providers, and infection preventionists. Extrinsic factors such as recently enacted legislation and mandatory reporting have not been closely examined in relation to changes in rates of HAI. The following review will examine evidence-based practices related to CLABSI and how they are reported, as well as how the Affordable Care Act, mandatory reporting, and pay-for-performance programs have affected these best practices related to CLABSI prevention. There is a disconnect in the methods and guidelines for reporting CLABSI between these programs, specifically among local monitoring agencies and the various federal oversight organizations. Future research will focus on addressing the gap in what defines a CLABSI and whether or not these programs to incentivize hospital to reduce CLABSI rates are effective.